Short-term influence analysis of different weights` instep weights on 50 meters speed and running time - Esquirol-Caussa, J.; Cos-Morera, M. A.; Palmada-Andreu, P.; Méndez-Olavide, M.; Padullés-Riu, J. M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Instep wearable resistances at running trainings(1) change mechanical parameters modifying muscle activity(2), ground plantar support and run biomechanics; changes could reduce lower limb`s impairment risk produced by abnormal stepping during the race(3). Instep weights show positive effects on the race, due to the influence of the instep specific placement without decreasing inter-muscular coordination nor altering running technique(2)(4)(5). Objective: to analyze if instep weights use during warm-up for 50-meter running series could significantly modify race times in sprinters and hurdlers and evaluate genders differences.